Neuroprotective activity of a virus‐safe nanofiltered human platelet lysate depleted of extracellular vesicles in Parkinson's disease and traumatic brain injury models - Liling Delila; Ouada Nebie; Nhi Thao Ngoc Le; Lassina Barro; Ming‐Li Chou; Yu‐Wen Wu; Naoto Watanabe; Masayasu Takahara; Luc Buée; David Blum; David Devos; Thierry Burnouf (Wiley, 2023)
Abstract Brain administration of human platelet lysates (HPL) is a potential emerging biotherapy of neurodegenerative and traumatic diseases of the central nervous system. HPLs being prepared from pooled platelet concentrates, thereby increasing viral risks, manufacturing processes should incorporate robust virus‐reduction treatments. We evaluated a 19 ± 2‐nm virus removal nanofiltration process using hydrophilic regenerated cellulose hollow fibers on the properties of a neuroprotective heat‐treated HPL (HPPL). Spiking experiments demonstrated >5.30 log removal of 20-22‐nm non‐enveloped minute virus of mice‐mock particles using an immuno‐quantitative polymerase chain reaction assay. The nanofiltered HPPL (NHPPL) contained a range of neurotrophic factors like HPPL. There was >2 log removal of extracellular vesicles (EVs), associated with decreased expression of pro‐thrombogenic phosphatidylserine and procoagulant activity. LC‐MS/MS proteomics showed that ca. 80% of HPPL proteins, including neurotrophins, cytokines, and antioxidants, were still found in NHPPL, whereas proteins associated with some infections and cancer‐associated pathways, pro‐coagulation and EVs, were removed. NHPPL maintained intact neuroprotective activity in Lund human mesencephalic dopaminergic neuron model of Parkinson's disease (PD), stimulated the differentiation of SH‐SY5Y neuronal cells and showed preserved anti‐inflammatory function upon intranasal administration in a mouse model of traumatic brain injury (TBI). Therefore, nanofiltration of HPL is feasible, lowers the viral, prothrombotic and procoagulant risks, and preserves the neuroprotective and anti‐inflammatory properties in neuronal pre‐clinical models of PD and TBI.